Pengembangan LKPD Berbasis Tri-N (Niteni, Nirokke, Nambahi) Pada Muatan Materi IPA Kelas IV Sekolah Dasar Palembang - Yusindra; Sylvia Lara Syaflin; A. Heryanto (Jurnal Elementaria Edukasia, 2023)
This research uses the Research and Development (R&D) research methodology. The aim of this development research is to produce Tri N-based LKPD in learning force and movement in class IV elementary school that is valid and practical. This research was conducted on 6 fourth grade students at SD Negeri 93 Palembang, using a limited trial. This limited trial basis was carried out to determine the feasibility of the Tri N-based LKPD product. Based on the results of the needs analysis, it is known that the learning process for class IV students at SD Negeri 93 Palembang is currently not optimal, considering the lack of student enthusiasm in participating in learning. LKPD developed using a TRI N-based method. Material expert validation results show a percentage of 55% (quite valid), media expert validation results show a percentage of 91% (very valid), and language expert validation results show a percentage of 80% (valid), meaning that the media has been declared valid in terms of material, media and language. The level of practicality of the TRI N (Niteni, Nirokke, Nambahi) based LKPD in grade IV science material, through student responses showed a score of 90.5%, which proves that the LKPD developed is very practical in its use. This is supported by teacher responses which show a practicality level of 96%. It was proven that during the limited trial, there was an increase in the test results of students who used the TRI N (Niteni, Nirokke, Nambahi) based LKPD on class IV science content, which initially obtained an average score of 64.2, increasing to 96.7.